Definition and analysis of the rules and procedures for the construction of a national model for sustainable development, with indicators of attraction of the area - Maurizio Turina; Giuseppe Confessore; Sandro Turina; Andrea Vignoli (European Regional Science Association (ERSA), 2011)
This study focused on issues of major industry consortia members to FICE (Italian Federation of Public Associations Industrialization) and selected by the association as a national case studies of excellence in order to answer research questions. The analysis of cases, together with the detection of a statistical nature already available, provided the information necessary to determine, albeit in a non-deterministic, conditions that should characterize an industry consortium to implement measures relevant to the development of business competitiveness premises. These conditions may serve as a 'reference point' toward which all should strive consortia. The structuring of a panel of performance indicators, land and its executive summary of the different indicators introduced the theme of one of the Indicator, the basic approach used demonstrates the validity of the methodology that has characterized the study as only the deviations of the Indicator areas object benchmark minor, a demonstration of the attractiveness of land that the indicator can assume in the areas of national excellence. In particular the action of 'benchmark' has made it possible to select seven selected cases, as well as their objective interest, with the intent to represent all the macro regions of the country where there are industry consortia. This methodology involves a transition from 'culture of knowledge' often characterized by theoretical models that are almost never experienced with short-term events, to a 'culture of know-how' characterized by a much more pragmatic approach aimed through the application of models simulation techniques and tools for decision support and the involvement of domain experts through the organization of the university masters functional 'concentration' of specific skills. FICE (Italian Federation of Public Associations Industrialization) is the Italian organization that brings together and represents the Consortium and organizations for the promotion and industrial development. Consortia are typically made up of chambers of commerce, local communities, financial institutions and business associations. The search result shows the validity of the methodology used since the deviations Indicator only in areas subject to minor benchmark a demonstration of the attractiveness of land that the indicator can assume in the areas of national excellence.
Keywords: 330